Implementasi Model Pembelajaran Inquiri Dengan Konsep Analogi Untuk Meningkatkan Hasil Belajar Fisika Materi Gerak Lurus Beraturan Dan Gerak Melingkar Beraturan - Sitania, Dano Samdan; Huliselan, Estevanus Kristian; Malawau, Seska (Pattimura University, 2022)
The aim of this study is to improve learning outcomes using the Inquiry learning model and Analogy Concept on Uniform Linear Motion and Uniform Circular Motion in students of SMA Negeri 4 Leihitu, Central Maluku Regency. The type of research is descriptive quantitative with one group pre-test post-test design. Analysis average normalized gain based on the initial and final test scores. The initial test results showed that all students (100%) were in the failed qualification. The lowest student achievement score is 2.63, and the highest is 18.42, with an average of 10.23. This condition indicates that students do not yet have the initial ability on Uniform Linear Motion and Uniform Circular Motion substance. After applying the Inquiry learning model and Analogy Concept in the teaching and learning process, the average score of the students' final test results was 89.18, which was in suitable qualification with the lowest score of 71.05 and the highest 97.37. Based on the average normalized gain analysis, the average normalized gain obtained 0.88, which is in the high category. This study indicates that the Inquiry learning model makes students more active in exploring knowledge to get information to solve problems given by educators so that students' memory of the substance is longer. In addition, teachers succeeded in instilling Uniform Linear Motion as the base domain, making it easier for students to understand Uniform Circular Motion as the target domain. Proves that using the Inquiry learning model with the Analogy Concept can change the activity and increase students' knowledge towards a better direction.